Revision of the Neotropical stick insect genus Ocnophila (Phasmatodea: Diapheromeridae) with a new species from Colombia - Ghirotto, Victor Morais; Engelking, Phillip Watzke; Crispino, Edgar Blois (Zootaxa, 2023)
The genus Ocnophila Brunner, 1907 is here redescribed with an emended diagnosis, containing three valid species from Venezuela and Colombia: Ocnophila integra Brunner, 1907 with Ocnophila signatior Brunner, 1907 syn. nov. as a new junior synonym, Ocnophila iphicla (Westwood, 1859) and Ocnophila serrata sp. nov. In addition to the description of the new species we redescribe O. integra and O. iphicla, also providing a description of the male genitalia for O. integra. For the other species previously contained in the genus, we synonymize Ocnophila brevifemur Brunner, 1907 syn. nov. and Ocnophila armata Brunner, 1907 syn. nov. under Pygirhynchus bispinosus (Redtenbacher, 1906), Ocnophila inaequalis Brunner, 1907 syn. nov. under Libethra venezuelica Brunner, 1907, and transfer the remaining species to other genera, resulting in the following new combinations: Agamemnon illegitimus (Brunner, 1907) comb. nov., A. poeyi (Bolívar, 1888) comb. nov., Canuleius nattereri (Brunner, 1907) comb. nov., C. pedestris (Brunner, 1907) comb. nov., Dyme acanthonota (Günther, 1930) comb. nov., D. borellii (Giglio-Tos, 1898) comb. nov., D. ramulus (Giglio-Tos, 1898) comb. nov., Exocnophila cornuta (Brunner, 1907) comb. nov., E. tuberculata (Brunner, 1907) comb. nov., Litosermyle inconspicua (Brunner, 1907) comb. nov., Lit. nana (Shelford, 1913) comb. nov., Lit. riveti (Shelford, 1913) comb. nov., Lit. submutica (Brunner, 1907) comb. nov., Libethra aculeata (Brunner, 1907) comb. nov., Libethroidea willemsei (Günther, 1935) comb. nov., Pygirhynchus fortior (Brunner, 1907) comb. nov., P. oryx (Westwood, 1859) comb. nov., P. scops (Kaup, 1871) comb. nov., Pseudosermyle meditans (Brunner, 1907) comb. nov., Sermyle aurita (Rehn, 1905) comb. nov., and S. ciliata (Brunner, 1907) comb. nov. Furthermore, Pygirhynchus carioca Piza, 1944 syn. nov. is synonymized under P. fortior comb. nov. We provide a description of the male and egg of Litosermyle Hebard, 1919, previously known only from females, through the illustration and redescription of Lit. inconspicua (Brunner, 1907) comb. nov. Finally, we include Dubiophasma Zompro, 2001, Exocnophila Zompro, 2001, Litosermyle, Ocnophila and Parocnophila Zompro, 1998 in Oreophoetini.